Defect engineering of UiO-66 for CO2 and H2O uptake – a combined experimental and simulation study. Issue 11 (15th February 2016) - Liang, Weibin; Coghlan, Campbell J.; Ragon, Florence; Rubio-Martinez, Marta; D'Alessandro, Deanna M.; Babarao, Ravichandar
Abstract : Defect concentrations and their compensating groups have been systematically tuned within UiO-66 frameworks and are found to have a pronounced effect on CO2 and H2 O adsorption at low and high pressure. Abstract : Defect concentrations and their compensating groups have been systematically tuned within UiO-66 frameworks by using modified microwave-assisted solvothermal methods. Both of these factors have a pronounced effect on CO2 and H2 O adsorption at low and high pressure.